(untitled) (Annals of Medical Research, 2021)
Aim: Ependymomas are highly heterogeneous neuroepithelial tumors that occur in all age groups and in all compartments of the central nervous system. Because of the tumor heterogeneity, the current histopathological criteria for grading are insufficient. Therefore, auxiliary prognostic markers that are cost-effective and easy-to-use and may help predict clinical behavior are still needed. Neural Epidermal Growth Factor Like Like-2 (NELL2) and laminin alpha-2 (LAMA2) are two outstanding proteins with prognostic significance in ependymomas. In the present study, we aimed to investigate the correlation of NELL2 and LAMA2 expression with histopathological parameters in patients with ependymomas. Materials and Methods: A total of 64 ependymomas were retrospectively evaluated and representative paraffin blocks were selected. Demographic and histopathological characteristics of the patients were noted. Slides from selected blocks were immunohistochemically stained using NELL2, LAMA2 and Ki67 antibodies. The results were compared with other characteristics of the patients. Results: We found that the histological grades of the ependymomas correlated with age, tumor localization, histological subtype and number of mitosis. NELL2 staining was significantly higher in grade II ependymomas, while LAMA2 staining was significantly higher in grade III ependymomas. Moreover NELL2 and LAMA2 expression was associated only with the histological grade of the tumor. We found the Ki-67 proliferation index to be consistent with increasing histological grade. Conclusions: Our findings show that higher NELL2 expression than LAMA2 expression is associated with low histological grade and probably better prognosis. On the other hand LAMA2 expression is associated with high histological grade and probably poor prognosis.